Riceberry bran as a potential source of anti-diabetic agents and its Riceberry bran powder - Ratananikom, Khakhanang; Nitisuk, Panorjit; Wongpreedee, Panida; Premprayoon, Kantapon; Kubola, Jittawan (Journal of Food Technology Research, 2024)
This study evaluated the anti-a-glucosidase effect, antioxidant activity, and total phenolic compounds of Riceberry bran extracts prepared by the extraction of Riceberry bran with distilled water, ethanol, or hexane using a maceration technique. The ethanolic extract resulted in the significantly highest a-glucosidase inhibitory activity, at 64.13±1.09%. The highest levels of antioxidant activity against 2,2-diphenyl-1-picrylhydrazyl and 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radicals were found in the aqueous extract with a half-maximal inhibitory concentration (IC50) of 0.26±0.001 and 0.13±0.001 mg/mL, respectively. Likewise, the total phenolic compounds of the aqueous extract were the highest at 36.20±1.80 mg GAE/g of extract. The Riceberry bran powder obtained by double drum drying was also examined for its physical and chemical properties. It was found that the Riceberry bran powder was of good quality and provided high levels of a-glucosidase inhibition (20.24±0.47%), antioxidant activities (IC50 for DPPH = 4.19±0.08 mg/mL, IC50 for ABTS = 1.57±0.07 mg/mL), and total phenolic compounds (31.25±1.32 mg GAE/g of powder). The overall results indicated the potential of Riceberry bran to provide a-glucosidase inhibitors, antioxidants, and phenolic compounds, which can be used as useful health promoters and nutraceuticals to combat diabetes, and its powder also had potential in the functional food industry.